THE NATURE OF PHYSIOLOGICAL LOAD IN THE TRAINING PROCESS IN RUNNING (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article examines and highlights the issues of physiological changes in the functional systems and organs of an athlete under the influence of track and field exercises, as well as the specifics of training in mid-mountain conditions and physiological criteria for selection in track and field.